State Continuity and Nationality: The Baltic States and Russia : Past, Present and Future as Defined by International Law. Second Revised Edition - Ziemele, Ineta, (Human Rights and Humanitarian Law E-Books Online, Collection 2026., 2026)
Political changes in Central and Eastern Europe in the 1990s led to important territorial changes and confronted decision-makers and international lawyers with complex questions relevant to State continuity and succession. The case of the Baltic States was particularly difficult since they re-emerged after half-a-century of Soviet occupation. In addition to questions on the status of new States, important issues arose with regard to the fate of nationals of the former federations, generating frantic international efforts in developing and consolidating available rules and principles on nationality in situations of territorial change. In this context, the Baltic case stood apart. It raised questions of non-recognition of consequences of their illegal occupation in international law, but that was not the way the issues were dealt with. The book documents and examines the story of the Soviet occupation of the Baltic States in 1940 and their claim to State continuity fifty years later. It brings in the issue of the obligations of Russia in this context. The book asks the question what nationality solutions had to be adopted in the region and shows the scrutiny they received from international institutions. This second edition of the book revisits decisions that were taken in the 1990s and asks whether they have withstood the test of time. The case of the Baltic States is an example of the strength of international law rules, when applied with courage, and of the risks, when too many compromises with rules and principles are accepted. Although the book is specific in its coverage, it is of general importance because it draws conclusions concerning developments in law and practice which are relevant for a better understanding and regulation of statehood and nationality in international law.